The “Lessons” of Britain’s counterinsurgency in Malaya: An American obsession - NGOEI, Wen-Qing (WEI Wenqing) (Institutional Knowledge at Singapore Management University, 2019)
This essay examines how US preoccupation with British counterinsurgency in Malaya exerted a profound impact on US Cold War policy in Vietnam and the Global South, and continues to have consequences for American interventions in the present.